Fabrication of Efficient and Stable CsPbI3 Perovskite Solar Cells through Cation Exchange Process. Issue 36 (16th August 2019) - Lau, Cho Fai Jonathan; Wang, Zhiping; Sakai, Nobuya; Zheng, Jianghui; Liao, Chwen Haw; Green, Martin; Huang, Shujuan; Snaith, Henry J.; Ho‐Baillie, Anita
Abstract: Inorganic lead halide perovskites have attracted attention due to their tolerance to higher processing temperature and higher bandgap suitable for tandem solar cell application. Not only do they improve cell stability and efficiency, they also reveal many interesting and un‐anticipated material qualities. This work reports a simple cation exchange growth (CEG) method for fabricating inorganic high‐quality cesium lead iodide (CsPbI3 ) by adding methylammonium iodide (MAI) additive in the precursor. X‐ray diffraction results reveal a multi‐stage film formation process whereby i) MAPbI3 perovskite first formed that acts as a perovskite template for ii) subsequent ion exchange whereby the MA + ions in the MAPbI3 are replaced by Cs + (as temperature ramps up) and iii) form g‐phase perovskite CsPbI3 . Optical microscopy, photoluminescence, and electrical characterizations reveal that the CEG process produces high‐quality film with better absorption, uniform and dense film with better interface, lower defects, and better stability. Using the CEG approach, the power conversion efficiency of the best CsPbI3 solar cell is significantly increased up to 14.1% for the device fabricated using 1.0m MAI additive. The outcome is beneficial for further improvement of inorganic perovskite solar cells and their application in perovskite‐silicon tandem devices. Abstract : Herein, a simple cation exchange growth (CEG) method is demonstrated that replaces the organic MA + cation with Cs + to produce a high‐quality black γ‐phase CsPbI3 perovskite device, enhancing both power conversion efficiency and stability. As a result, the device fabricated using the optimized CEG method yields efficiency up to 14.1%.